Consecutive Three‐Component Synthesis of 2, 6‐Disubstituted Pyrimid‐4(3H)‐ones and 1, 5‐Disubstituted 3‐Hydroxypyrazoles Initiated by Copper(I)‐Catalyzed Carboxylation of Terminal Alkynes. Issue 14 (3rd September 2014) - Schreiner, Ella; Braun, Stephan; Kwasnitschka, Christiane; Frank, Walter; Müller, Thomas J. J.
Abstract A copper(I)‐catalyzed carboxylation of terminal alkynes followed trapping of the carboxylate with methyl iodide provides a straightforward access to 3‐substituted methyl propiolates that can be reacted in the same reaction vessel in a consecutive fashion to give 2, 6‐disubstituted pyrimid‐4(3H)‐ones and 1, 5‐disubstituted 3‐hydroxypyrazoles in moderate to good yields. The Cu(I)‐catalyzed carboxylation with carbon dioxide as C1 source therefore provides an environmentally benign entry to three‐carbon building blocks in heterocyclic synthesis. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>